Unraveling the supply-service relationship between high-speed railway and conventional railway: A temporal perspective - Zhang, Guangxia; Liu, Yanfang; Jing, Ying; Chen, Huiting; Wang, Yiheng; Wang, Zhengyu (Frontiers in Environmental Science, 2023)
With the rapid development of high-speed railway (HSR) in China, the whole railway system evolves into complex network with hierarchical characteristics and satisfy people’s multiple transportation needs. Though many scholars have studied the discrepancy between HSR and air travel or inter-city coach, few studies have involved the potential supply service competition within the railway system. This article explores the supply-service relationship between HSR and conventional railway (CR) of core cities in China from a temporal perspective based on the train schedules. Results are: (1)The HSR network has higher service intensity and has more advantages in the south China, and the CR network covers a wider range of space and has more advantages in the north China. (2)HSR has very few trains running at night, so that 88.33% of the services are of high quality, while the superior service rate of CR is only 51.08%. (3)Among the services whose time difference index is within 1 hour, 59.01% of HSR services can be replaced, while up to 74.05% of CR services are at risk of being replaced. Spatially, HSR and CR services are more likely to generate temporal substitution on the mainline, but temporal complementarity between city pairs on non-arterial lines. The operational strategy of the railway passenger system can be better understood through recognizing the service relationship between HSR and CR. This study facilitates railway authorities to optimize the supply-service strategies for national sustainable development.